2022
DOI: 10.3390/ijerph19053045
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Parameters, Physical Activity, Physical Fitness, and Executive Functions among Primary School Children

Abstract: Physical activity during childhood and adolescence favors brain development and cognitive functioning, particularly the executive functions. This study aimed to assess potential associations between anthropometric parameters, physical activity, physical fitness, and executive functions among elementary school children returning to school after the COVID-19 lockdown in Chile. School-age male and female participants (n = 90; age, 10–12 years) participated in the study. To determine the association between variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
0
8
0
1
Order By: Relevance
“…As previously described, the justification for these results could be situated in evidence that previously highlighted that the regular practice of physical activity at a certain intensity leads to changes in the structure and functionality of the brain, optimizing its development and contributing to improving brain plasticity [15,25,26,54]. These findings were also previously discussed in a review conducted by Ruiz-Ariza et al [55].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As previously described, the justification for these results could be situated in evidence that previously highlighted that the regular practice of physical activity at a certain intensity leads to changes in the structure and functionality of the brain, optimizing its development and contributing to improving brain plasticity [15,25,26,54]. These findings were also previously discussed in a review conducted by Ruiz-Ariza et al [55].…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have demonstrated the relationship between physical exercise and the development of cognitive skills, such as attention, memory, or inhibitory control, during this stage through various interventions. Some authors [15][16][17] have suggested that cognitive benefits are one of the consequences of the numerous neurophysiological changes that occur when engaging in regular physical exercise with a certain intensity. Therefore, it is important not only to determine the amount of activity school children engage in but also to assess their level of physical fitness [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive functions are essential skills for adolescents’ healthy physical and mental development, success in school and life, and cognitive, social, and psychological development ( 8–19 ). On the contrary, when children and adolescents have executive function deficits, such as attention deficit hyperactivity disorder (ADHD) and aggressive behaviors, it can cause heavy psychological and physical stress on the family ( 20 , 21 ). Thus, executive function plays an important role in the healthy development of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…On top of the three core executive functions, the brain builds higher-order executive functions, such as logical reasoning, problem solving, and task planning, with the three subcomponents being both independent and interrelated (7). Executive functions are essential skills for adolescents' healthy physical and mental development, success in school and life, and cognitive, social, and psychological development (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). On the contrary, when children and adolescents have executive function deficits, such as attention deficit hyperactivity disorder (ADHD) and aggressive behaviors, it can cause heavy psychological and physical stress on the family (20, 21).…”
Section: Introductionmentioning
confidence: 99%